The Gallerani Account Book of 1305-1308. - Nobes, Christopher W. (The Accounting Review, 1982)
ABSTRACT: This paper examines the account book of an Italian firm operating in London in the early 14th century. The existence of the book is well known to accounting historians, but it has not previously been carefully studied by them. The history of the firm and of the book are discussed, followed by an examination of the treatment of cash and non-cash entries and of opening and closing procedures. The presence of accounts for joint-ventures, petty cash, expenses, profit, and capital; the use of a single monetary unit; the consistent method of recording; and the achievement of balance at the end of an accounting period are features that may justify a claim that this account book was part of a double-entry system.